Pengenalan Literasi Keuangan bagi Santri Pondok Pesantren: Membangun Generasi Melek Finansial - Fietroh, Muhammad Nur; Aprirachman, Rozzy; Nurasia, Nurasia; Purnama, yuni; Salam, Abdul; Sanjani, Muhammad Rafi'i; Oktapiani, Sherli; Santoso, Agus; Busman, Sherwin; Nuryani, Hanifah Sri; Mandasari, Jayanti; Ananda, Nova Aditya; Cita, Fitria Permata; Andriani, Sri; Irawan, Edi; Sugiarto, Aris; NurJihadi, Muhammad; Rusni, Andi (Civiliza Publishing, 2024)
This community service aims to improve Islamic financial literacy among students of Al-Mutmainnah Islamic Boarding School. The methods used are material presentation, discussion, and Q&A. The materials presented include the definition of financial literacy and inclusion as well as Islamic financial literacy, its benefits, and types of Islamic financial products and services. The results of the activity show that the level of understanding of Islamic financial literacy among students has increased. Students also showed a high interest in learning and applying finance in everyday life. This activity is expected to help students manage their finances wisely, independently, and contribute to the development of the Islamic boarding school and community economy.